2021
DOI: 10.1017/s0007114521004062
|View full text |Cite
|
Sign up to set email alerts
|

Betaine supplementation fails to improve body composition: a systematic review and meta-analysis

Abstract: Previous studies evaluating the effects of betaine supplementation on body composition offer contradictory findings. This systematic review and meta-analysis assessed the effects of betaine supplementation on body composition indices (body mass [BM], body mass index [BMI], body fat percentage [BFP], fat mass [FM], fat-free mass [FFM]), and dietary intakes. Studies examining the effects of betaine supplementation on body composition and dietary intakes published up to August 2021 were identified through PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…After a fourteen-week period, biochemical analyses revealed increased testosterone levels in supplemented individuals, while there were no significant changes in lean body mass or body fat. According to a meta-analysis by Ashtary-Larky et al [ 98 ], betaine supplementation does not improve body composition. No significant changes in body composition indices, such as body mass, body mass index, body fat percentage, fat mass, or fat-free mass, were noted.…”
Section: Health-promoting Propertiesmentioning
confidence: 99%
“…After a fourteen-week period, biochemical analyses revealed increased testosterone levels in supplemented individuals, while there were no significant changes in lean body mass or body fat. According to a meta-analysis by Ashtary-Larky et al [ 98 ], betaine supplementation does not improve body composition. No significant changes in body composition indices, such as body mass, body mass index, body fat percentage, fat mass, or fat-free mass, were noted.…”
Section: Health-promoting Propertiesmentioning
confidence: 99%
“…Also, a study of men in a strength training program found that betaine supplementation for 6 weeks improved body composition by lowering body fat and fat mass and increasing lean body mass compared with placebo [30]. However, meta-analyses of clinical trials in humans found that dietary betaine supplementation did not affect body mass [31,32], similar to healthy cats [23]. Body fat was lowered with betaine supplementation [32], so the effects of betaine on body mass may depend on the species, kidney function status, and/or high metabolic demand.…”
Section: Discussionmentioning
confidence: 99%